Does First-Trimester Screening Modify the Natural History of Congenital Heart Disease? Analysis of Outcome of Regional Cardiac Screening at 2 Different Time Periods - Jicinska, Hana; Vlasin, Pavel; Jicinsky, Michal; Grochova, Ilga; Tomek, Viktor; Volaufova, Julia; Skovranek, Jan; Marek, Jan (Circulation, 2017)
BACKGROUND: The study analyzed the impact of first-trimester screening on the spectrum of congenital heart defects (CHDs) later in pregnancy and on the outcome of fetuses and children born alive with a CHD. METHODS: The spectrum of CHDs, associated comorbidities, and outcome of fetuses, either diagnosed with a CHD in the first trimester (Group I, 127 fetuses) or only in the second-trimester screening (Group II, 344 fetuses), were analyzed retrospectively between 2007 and 2013. Second-trimester fetuses diagnosed with a CHD between 2007 and 2013 were also compared with Group III (532 fetuses diagnosed with a CHD in the second trimester from 1996 to 2001, the period before first-trimester screening was introduced). RESULTS: The spectrum of CHDs diagnosed in the first and second trimesters in the same time period differed significantly, with a greater number of comorbidities (P<0.0001), CHDs with univentricular outcome (P<0.0001), intrauterine deaths (P=0.01), and terminations of pregnancy (P<0.0001) in Group I compared with Group II. In Group III, significantly more cases of CHDs with univentricular outcome (P<0.0001), intrauterine demise (P=0.036), and early termination (P<0.0001) were identified compared with fetuses diagnosed with CHDs in the second trimester between 2007 and 2013. The spectrum of CHDs seen in the second-trimester groups differed after first-trimester screening was implemented. CONCLUSIONS: First-trimester screening had a significant impact on the spectrum of CHDs and the outcomes of pregnancies with CHDs diagnosed in the second trimester. Early detection of severe forms of CHDs and significant comorbidities resulted in an increased pregnancy termination rate in the first trimester.
Keywords: echokardiografie; plod; Female; Heart Defects, Congenital; ženské pohlaví; Pregnancy Trimester, Second; komorbidita; congenital heart defects; lidé; Fetus; Comorbidity; těhotenství; druhý trimestr těhotenství; Pregnancy Trimester, First; Echocardiography; epidemiology; Ultrasonography, Prenatal; retrospektivní studie; first-trimester screening; chromozomální aberace; Czech Republic; echocardiography; Česká republika; prenatal cardiology; vrozené srdeční vady; Pregnancy; ultrasonografie prenatální; Retrospective Studies; první trimestr těhotenství; Chromosome Aberrations; Humans